2000
DOI: 10.1348/096317900167056
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of personal statements and the role of the five‐factor model of personality in relation to medical training

Abstract: This paper explores the role of personality, and the predictive validities of personal statements (PSs) and previous academic performance in relation to future performance in medical training. One hundred and seventy-six medical students had their application PSs coded into information categories and were followed over a 1-year period and assessed on (1) 21 diVerent assessments (observations, exams, essays, etc.) and (2) the dimensions of the ve-factor model (FFM) of personality. Neither the PS information cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 53 publications
4
83
2
2
Order By: Relevance
“…Our research confirmed the utility of taking into account anxiety and depression as predictors of success in a medical profession, which has been already suggested in the literature (Pamphlett & Farnill 1995;Stewart et al 1999). At the same time, our study has introduced the concept of personality factor, which constitutes a global measure of the level of personality integration in terms of the SOC and coping styles, which broadens the list of universal psychological variables presented in the literature, which are useful for the purpose of describing the phenomenon in question (Jones 1991;Lacorte & Risuci 1993;Collins et al 1995;Pamphlett & Farnill 1995;Stewart et al 1999;Ferguson et al 2000Ferguson et al , 2002Ferguson et al , 2003Finset et al 2005;Gude et al 2005;Julian 2005;Peskun et al 2007). Therefore, success in a medical career seems to be a consequence of the level of personality structure integration, and not a simple result of the medical education process.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our research confirmed the utility of taking into account anxiety and depression as predictors of success in a medical profession, which has been already suggested in the literature (Pamphlett & Farnill 1995;Stewart et al 1999). At the same time, our study has introduced the concept of personality factor, which constitutes a global measure of the level of personality integration in terms of the SOC and coping styles, which broadens the list of universal psychological variables presented in the literature, which are useful for the purpose of describing the phenomenon in question (Jones 1991;Lacorte & Risuci 1993;Collins et al 1995;Pamphlett & Farnill 1995;Stewart et al 1999;Ferguson et al 2000Ferguson et al , 2002Ferguson et al , 2003Finset et al 2005;Gude et al 2005;Julian 2005;Peskun et al 2007). Therefore, success in a medical career seems to be a consequence of the level of personality structure integration, and not a simple result of the medical education process.…”
Section: Discussionmentioning
confidence: 91%
“…The personality trait most often indicated as a positive predictor of high achievement during medical school and future success in the medical career was 'conscientiousness' (Huxham et al 1980;Hobfoll & Benor 1981;Jones 1991;Ferguson et al 2000;Skommer & Gromadecka-Sutkiewicz 2005). In one of the studies, however, it was found that Practice points .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, extraverts seem to have the personality attributes needed to perform better in educational environments that require interpersonal interactions (Ferguson et al 2000). Therefore, one can expect that those who score high on the Extraversion factor would not perform as well as their introverted counterparts in the preclinical phase of medical education.…”
Section: Selected Personality Instruments Frequently Used In Medical mentioning
confidence: 99%
“…The FFM dimensions and their operational manifestations primarily represent the normal range of individual differences, contrary to many clinically developed personality descriptive models, making the model suitable for studying traits and samples derived from the general population [19]. The FFM may serve as a uniform, comprehensive and robust framework for describing medical, medical sciences and biomedical students' personality characteristics and for substantially advancing our understanding whether these traits relate to academic success [19,20]. Therefore, this study was carried by using the FFM of personality to assess the relationship between types of personality and level of academic performance among the health sciences students of two faculties in the Management and Science University, Malaysia.…”
Section: Introductionmentioning
confidence: 99%